Effects of Strengthening Exercises on Swallowing Musculature and Function in Senior Healthy Subjects: a Prospective Effectiveness and Feasibility Study - Kraaijenga, S. A. C.; van der Molen, L.; Stuiver, M. M.; Teertstra, H. J.; Hilgers, F. J. M.; van den Brekel, M. W. M. (Dysphagia, 2015)
Head and neck cancer (HNC) patients may develop dysphagia due to muscle atrophy and fibrosis following chemoradiotherapy. Strengthening of the swallowing muscles through therapeutic exercise is potentially effective for improving swallowing function. We hypothesize that a customized Swallow Exercise Aid (SEA), developed for isometric and isokinetic strengthening exercises (against resistance), can help to functionally strengthen the suprahyoid musculature, which in turn can improve swallowing function. An effectiveness/feasibility study was carried out with ten senior healthy volunteers, who performed exercises 3 times per day for 6 weeks. Exercises included chin tuck against resistance (CTAR), jaw opening against resistance (JOAR), and effortful swallow exercises with the SEA. Multidimensional assessment consisted of measurements of maximum chin tuck and jaw opening strength, maximum tongue strength/endurance, suprahyoid muscle volume, hyoid bone displacement, swallowing transport times, occurrence of laryngeal penetration/aspiration and/or contrast residue, maximum mouth opening, feasibility/compliance (questionnaires), and subjective swallowing complaints (SWAL-QOL). After 6-weeks exercise, mean chin tuck strength, jaw opening strength, anterior tongue strength, suprahyoid muscle volume, and maximum mouth opening significantly increased ( p < .05). Feasibility and compliance (median 86 %, range 48–100 %) of the SEA exercises were good. This prospective effectiveness/feasibility study on the effects of CTAR/JOAR isometric and isokinetic strengthening exercises on swallowing musculature and function shows that senior healthy subjects are able to significantly increase swallowing muscle strength and volume after a 6-week training period. These positive results warrant further investigation of effectiveness and feasibility of these SEA exercises in HNC patients with dysphagia.